Tales from a not-so-happily ever after - Russell, Rachel Renée; Russell, Nikki; Russell, Erin (Russell, Rachel Renée. Dork diaries, 2014)
A bump on the head suffered during gym class causes middle school drama queen Nikki Maxwell to have a crazy dream where all of her acquaintances assume the roles of familiar fairy tale characters.